2005
DOI: 10.1093/jxb/eri142
|View full text |Cite
|
Sign up to set email alerts
|

VvHT1 encodes a monosaccharide transporter expressed in the conducting complex of the grape berry phloem

Abstract: The accumulation of sugars in grape berries requires the co-ordinate expression of sucrose transporters, invertases, and monosaccharide transporters. A monosaccharide transporter homologue (VvHT1, Vitis vinifera hexose transporter 1) has previously been isolated from grape berries at the veraison stage, and its expression was shown to be regulated by sugars and abscisic acid. The present work investigates the function and localization of VvHT1. Heterologous expression in yeast indicates that VvHT1 encodes a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 34 publications
10
82
1
Order By: Relevance
“…In contrast, SUREs are absent from the VvHT5 promoter region and VvHT5 transcription has been shown to be insensitive to sugar regulation in grape suspension cells (Conde et al, 2006). This further reinforces the hypothesis that, unlike VvHT1 and VvHT3, which appear to be predominantly involved in hexose transport in developing leaves and berries (Vignault et al, 2005;Hayes et al, 2007), VvHT5 appears to have a specific role in enhancing sink strength under stress conditions and that this is controlled through ABA.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In contrast, SUREs are absent from the VvHT5 promoter region and VvHT5 transcription has been shown to be insensitive to sugar regulation in grape suspension cells (Conde et al, 2006). This further reinforces the hypothesis that, unlike VvHT1 and VvHT3, which appear to be predominantly involved in hexose transport in developing leaves and berries (Vignault et al, 2005;Hayes et al, 2007), VvHT5 appears to have a specific role in enhancing sink strength under stress conditions and that this is controlled through ABA.…”
Section: Discussionsupporting
confidence: 70%
“…This indicates that the role of VvHT5 is not to specifically increase hexose transport across the plasma membrane of powdery mildew-infected epidermal cells but rather to enhance the supply of sugar from the phloem to the surrounding tissues during the transition from source to sink. Vignault et al (2005) previously showed VvHT1 to be localized to the plasma membrane of the sieve element/companion cell interface in developing grape berries, and the location of VvHT5 promoter-directed expression in Arabidopsis appears to be similar. However, further work will be required to confirm the exact cellular location within the vascular complex of grapevine leaves.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Seven plasma membrane monosaccharide transporter homologs (VvHTs) and a plastidic Glc transporter (pGLT) have been cloned from grape berries (Vignault et al, 2005;Hayes et al, 2007). Specific primers were designed for the sequences of VvHT1 (accession no.…”
Section: Overexpression Of Vvsk1 In Grapevine Cells Affects Sugar Tramentioning
confidence: 99%